New business models for electric cars: A holistic approach - Christian Lerch; Fabian Kley; David Dallinger (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2010)
Climate change and global resource shortages lead to a rethinking of classic individual mobility basing on combustion engines. As a result of technological improvements first electric vehicles are introduced and further market penetrations can be expected. But due to a possible wider implementation of battery-powered electrical propulsion systems in future, new challenges arise for both the classic automotive industry and further new players, e.g. battery manufacturers, the power supply industry or other service providers. Due to the various application cases of electric vehicles discussed topically, numerous business models can emerge leading to new shares in the value creation and involving new participating players. Consequently, the individual stakeholders are uncertain as to which business models are really effective with regard to targeting a profitable overall concept. Therefore, the aim of this contribution is to define a holistic approach to developing business models for electric mobility, regarding the holistic system on the one hand and giving decision support for concerning enterprises on the other hand. For this, the basic elements of electric mobility will be observed and topical approaches for business models for various stakeholders will be discussed. The paper closes with a systemic instrument for business models basing on morphological methods.
urn:nbn:de:0011-n-1392705
Keywords: 330; business models; electric vehicles; morphologic box; Elektrofahrzeug; Geschäftsmodell; Zukunftsforschung